Mathematics Teachers’ Practice Level of Alternative Evaluation Strategies and Tools in Basic Education in Sultanate of Oman - Al-Mandharia, Manal Abdulrahman; Al-Riyami, Mohammed Nassir (Journal of Educational and Psychological Sciences, 2020)
The aim of this study was to investigate the degree of mathematics teachers’ practice of authentic evaluation strategies and tools in the basic education stage in the Sultanate of Oman. The researcher prepared a questionnaire to measure the degree of use of the authentic evaluation strategies and tools. The sample consisted of (266) teachers where (211) teachers from the first cycle and (55) teachers from the second cycle of basic education schools in the province of Muscat. After statistical processing using averages, frequencies and tests, the results of the study showed that the teachers’ use of authentic evaluation strategies and tools in both the first and second cycles in the basic education schools was high. The results showed that the strategies of self-evaluation and peer evaluation are the most widely used by the teachers. The strategy of evaluating the performance by the concept's maps obtained the least degree of use although it has a high level. The results also showed that there are statistically significant differences in the degree of practice the authentic evaluation strategies and these differences are in favor of the teachers who have an experience of more than ten years. The results showed no statistically significant differences among the teachers of both the first and second cycles in the practice of authentic evaluation strategies and tools. Consequently, the researcher recommended directing the institutions that are responsible for the preparation of new teachers to add training programs on authentic evaluation strategies and tools. The researcher also recommended conducting studies on the difficulties faced by teachers on the practice of all authentic evaluation strategies and tools in a balanced manner.
Keywords: authentic evaluation strategies; authentic evaluation tools; basic education